2021
DOI: 10.3390/cancers13225668
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor FEZF1, a Direct Target of EWSR1-FLI1 in Ewing Sarcoma Cells, Regulates the Expression of Neural-Specific Genes

Abstract: Ewing sarcoma is a rare pediatric tumor characterized by chromosomal translocations that give rise to aberrant chimeric transcription factors (e.g., EWSR1-FLI1). EWSR1-FLI1 promotes a specific cellular transcriptional program. Therefore, the study of EWSR1-FLI1 target genes is important to identify critical pathways involved in Ewing sarcoma tumorigenesis. In this work, we focused on the transcription factors regulated by EWSR1-FLI1 in Ewing sarcoma. Transcriptomic analysis of the Ewing sarcoma cell line A673 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…With the inclusion of EWS/FLI mediated chromatin loops, we identified 193 genes that are dysregulated by a conserved EWS/FLI peak associated with a gained loop in EF-Endo versus EF-KD. These include genes that were previously shown to be EWS/FLI responsive and play important roles in tumor growth and/or metastasis in Ewing sarcoma, such as NKX2-2 ( 8 , 15 ), PPP1R1A ( 70 ), HOXD13 ( 71 ), FEZF1 ( 11 , 72 ), CCND1 ( 15 , 73 ) and CAV1 ( 74 ). We also identified target genes that code for surface proteins, such as SLC24A3 , NTNG1 , LINGO1 and PAPPA , reported as potential candidates for antibody-mediated therapies in Ewing sarcoma ( 75 , 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the inclusion of EWS/FLI mediated chromatin loops, we identified 193 genes that are dysregulated by a conserved EWS/FLI peak associated with a gained loop in EF-Endo versus EF-KD. These include genes that were previously shown to be EWS/FLI responsive and play important roles in tumor growth and/or metastasis in Ewing sarcoma, such as NKX2-2 ( 8 , 15 ), PPP1R1A ( 70 ), HOXD13 ( 71 ), FEZF1 ( 11 , 72 ), CCND1 ( 15 , 73 ) and CAV1 ( 74 ). We also identified target genes that code for surface proteins, such as SLC24A3 , NTNG1 , LINGO1 and PAPPA , reported as potential candidates for antibody-mediated therapies in Ewing sarcoma ( 75 , 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another developmental TF, RUNX3, can directly interact with EWS::FLI1 and coordinately regulate a subset of activated and repressed target genes ( 80 ). For FEZF1, a TF involved in nervous system development, 38% of FEZF1-regulated genes are also EWS::FLI1 target genes ( 81 ). In addition, EWS::FLI1 directly activates E2F family TFs, specifically E2F3, which positively regulate EWS::FLI1-activated genes and promote proliferation ( 82 , 83 ).…”
Section: Cell Autonomous Regulators Of Ews::fli1 Transcript Expressionmentioning
confidence: 99%
“…A recent study found that 14% of all TFs are regulated by EWS::FLI1, resulting in cascading downstream effects on the cell transcriptome ( 81 ). In addition to the TFs mentioned above, EWS::FLI1 can modulate the expression of the Hedgehog signaling mediator GLI1 ( 83 , 93 ), pluripotency TF SOX2 ( 38 , 51 ), the neural crest and myogenic developmental TF PAX7 ( 94 , 95 ), neurodevelopmental TF EGR2 ( 96 , 97 ), the blood and bone developmental TF SOX6 ( 45 ), FOXO1 ( 98 ), and AP1 ( 99 ).…”
Section: Cell Autonomous Regulators Of Ews::fli1 Transcript Expressionmentioning
confidence: 99%
“…Thus, deciphering the contribution of specific genes to Ewing sarcoma phenotypes is relevant to understanding Ewing sarcoma biology and identifying pathways involved in proliferation and migration/invasiveness. Our research group has predominantly focused on looking up genes regulated positively or negatively by EWSR1::FLI1 in Ewing sarcoma cells (e.g., NR0B1/DAX1, CCK, LOX, SPRY1, DKK2, or FEZF1) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%